Pediatric Cancer Recognition Training in Botswana - Jeremy S. Slone MD, MPH; Elise Ishigami MPH; Parth S. Mehta MD, MPH (SAGE Publishing, 2016)
Delayed presentation of children with cancer is a significant barrier to improving the survival from children's cancer in low- and middle-income countries (LMICs). Botswana, a country of approximately 2 million people in southern Africa, has only 1 pediatric cancer treatment program, based at Princess Marina Hospital (PMH) in the capital of Gaborone. A pediatric cancer recognition training program was developed that reached 50% of the government hospitals in Botswana teaching 362 health care workers how to recognize and refer children with cancer to PMH. Through evaluation of attendees, limitations in pediatric cancer training and general knowledge of pediatric cancer were identified. Attendees demonstrated improvement in their understanding of pediatric cancer and the referral process to PMH following the workshop.